Dakwah Management for Generation Z: Digital Media Integration, Institutional Branding, and Non-Formal Approaches in the Digital Revolution Era - Roa'zah, Nandipah; Muazaroh, Muslimatun Diana; Afifah, Diana Elfiyatul; Sukirno, Sukirno; Nuruzzaman, Moh. Agil; Supeno, Supeno; Munahar, Munahar; Hidayat, Muhammad Arif (Westscience Press, 2024)
This study aims to analyze the components of da'wah management relevant to Generation Z (Gen Z) through a literature review of various recent studies on digital da'wah, communication strategies, and media behavior of the younger generation. Gen Z is a group that is very familiar with technology, has a preference for visual, interactive content, and informal communication, thus requiring an updated da'wah strategy that differs from conventional approaches. The results of the study indicate that the effectiveness of da'wah for Gen Z is largely determined by the integration of digital media such as TikTok, Instagram, YouTube, and podcasts, which serve as their primary information consumption spaces. In addition, branding of da'wah institutions plays a significant role in building the image, credibility, and emotional engagement of young audiences. Informal da'wah approaches through community spaces, cafes, and creative events have also proven more resonant for Gen Z because they support participation and psychological closeness. However, digital da'wah faces challenges such as competition with entertainment content, the risk of message simplification, and low digital literacy in some da'wah institutions. This study concludes that preaching to Gen Z requires an innovative, participatory, and branding-based multi-channel approach, accompanied by strengthening digital capacity to ensure the sustainability of preaching in the modern era.